The evolution of costly displays, cooperation, and religion. Inferentially potent displays and their implications for cultural evolution - Joseph Henrich (Max Planck Institute of Economics, 2007)
This paper lays out an evolutionary theory for the cognitive foundations and cultural emergence of the extravagant displays (e.g., ritual mutilation, animal sacrifice, and martyrdom) that have so often tantalized social scientists, as well as more mundane actions that influence cultural learning and historical processes. In Part I, I use the logic of natural selection to build a theory for how and why seemingly costly displays influence the cognitive processes associated with cultural learning - why do "actions speak louder than words." The core idea is that cultural learners can avoid being manipulated by their potential models (those they are inclined to learn from) if they are biased toward models whose actions/displays would seem costly to the model if he held beliefs different from those he expresses verbally. I call these actions inferentially potent displays. Predictions are tested with experimental work from psychology. In Part II, I examine the implications for cultural evolution of this evolved bias in human cultural learning. The formal analytical model shows that this learning bias creates evolutionarily stable sets of interlocking beliefs and individually-costly practices. Part III explores how cultural evolution, driven by competition among groups or institutions stabilized at alternative sets of these interlocking belief-practice combinations, has led to the association of costly acts, often in the form of rituals, with deeper commitments to group beneficial ideologies, higher levels of cooperation within groups, and greater success in competition with other groups or institutions. Predictions are explored with existing cross-cultural, ethnographic, ethnohistorical and sociological data. I close by briefly sketching some further implications of these ideas for the study of religion and ritual.
Keywords: 330; Kulturpsychologie; Religion; Evolutionsökonomik; Kognition; Sozialer Wandel